1973
DOI: 10.1126/science.182.4117.1096
|View full text |Cite
|
Sign up to set email alerts
|

Birth Order, Family Size, and Intelligence

Abstract: The relation of birth order and family size to intellectual performance, as measured by the Raven Progressive Matrices, was examined among nearly all of 400,000 19-year-old males born in the Netherlands in 1944 through 1947. It was found that birth order and family size had independent effects on intellectual performance. Effects of family size were not present in all social classes, but effects of birth order were consistent across social class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(46 citation statements)
references
References 16 publications
3
37
0
1
Order By: Relevance
“…Further the probability of having twins at last birth might be a¤ected by certain characteristics of parents, such as their educational attainment. Results from linear probability models show however that the education of both the father and the mother have no signi…cant e¤ect on the probability of having twins at last birth, for both data sets 8 . These results indicate that the instrument twins at last birth has no separate e¤ect on the educational attainment of the …rst-born child, although this remains of course an untestable assumption.…”
Section: Instrumental Variables Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Further the probability of having twins at last birth might be a¤ected by certain characteristics of parents, such as their educational attainment. Results from linear probability models show however that the education of both the father and the mother have no signi…cant e¤ect on the probability of having twins at last birth, for both data sets 8 . These results indicate that the instrument twins at last birth has no separate e¤ect on the educational attainment of the …rst-born child, although this remains of course an untestable assumption.…”
Section: Instrumental Variables Resultsmentioning
confidence: 89%
“…Most of these studies have found a signi…cant negative relation between the number of children and the educational achievements of those children. Belmont and Marolla (1973) use a sample of around 400,000 19-year-old males born in the Netherlands between 1944 and 1947. They …nd a negative relation between family size and intellectual performance, measured as the score on a military examination (Raven Progressive Matrices).…”
Section: Family Size and Educational Attainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Galton found more firstborn sons in prominent positions than what he attributed to chance. This was the start of numerous studies; one of the most influential was a Science publication in 1973 showing a negative association between birth order and intelligence in young Dutch men (2). Since then, sociologists, psychologists, and demographers have proposed several explanatory models (3).…”
mentioning
confidence: 99%
“…Family size is a constant for every child of the household and captures unobserved information at the household level. On the other hand, birth order is an individual (child) level instrument that differs between siblings and, controlling for family size in a multivariate regression, it is unrelated to parents' background or fertility decisions (Belmont and Marolla 1973;Black, Devereux, and Salvanes 2011). As such, we wish to estimate the effect of birth order on academic attainment through its (negative) association with parental involvement and conditional on (at least) family size.…”
Section: Discussion Of the Assumptionsmentioning
confidence: 99%